(untitled) (Research, Society and Development, 2023)
Sleep, considered as a brain state of unconsciousness that can be altered by waking up, is common to all living beings, in addition to being one of the most important behavior patterns. It aims to evaluate the quality of sleep and the level of sleepiness of nursing professionals in a public hospital of high and medium complexity in the interior of Pará. This is a field study, with a quantitative character, of the statistical-descriptive type and cross-sectional, carried out with 164 nursing professionals. For data collection, an adapted sociodemographic questionnaire, the Pittsburgh Sleep Quality Index (PSQI) and the Epworth Sleepiness Scale (ESS) were used. Of the nursing professionals, 65.9% had poor sleep quality, 68.3% of the total are nursing technicians and 69.4% work in the morning shift. 38.4% had a normal daytime sleepiness index. Most professionals had poor sleep quality, however, the indices did not prove to be correlated with daytime sleepiness indices.